2021
DOI: 10.4110/in.2021.21.e25
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between NCR+ILC3s and the Microbiome in the Airways Shape Asthma Severity

Abstract: Asthma is a heterogeneous disease whose development is shaped by a variety of environmental and genetic factors. While several recent studies suggest that microbial dysbiosis in the gut may promote asthma, little is known about the relationship between the recently discovered lung microbiome and asthma. Innate lymphoid cells (ILCs) have also been shown recently to participate in asthma. To investigate the relationship between the lung microbiome, ILCs, and asthma, we recruited 23 healthy controls (HC), 42 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…We observed a negative relationship between ILC3 levels and bacterial richness, as measured by OTU in nasal scrapings. This finding supports previous research showing that ILC3 is a marker of dysbiosis [30,31]. However, because increased ILC3 levels were associated with lower bacterial richness, they did not significantly affect the clinical severity of chronic rhinosinusitis.…”
Section: Ilc3 and Bacterial Richnesssupporting
confidence: 90%
“…We observed a negative relationship between ILC3 levels and bacterial richness, as measured by OTU in nasal scrapings. This finding supports previous research showing that ILC3 is a marker of dysbiosis [30,31]. However, because increased ILC3 levels were associated with lower bacterial richness, they did not significantly affect the clinical severity of chronic rhinosinusitis.…”
Section: Ilc3 and Bacterial Richnesssupporting
confidence: 90%
“…ILC3s are divided into 2 subtypes depending on their expression of the NCR NKp46, and NCR - ILC3s are known to predominantly produce IL-17 in the presence of IL-1β 47 . Although these cells are less clearly defined in asthma, recent studies have revealed the contribution of ILC3s to lung dysfunction and asthma severity 48 . Moreover, the proliferation of IL-17-producing ILC3s induced by NLRP3 activation in the lungs was suggested to directly drive airway hyperresponsiveness, which was ameliorated by the blockade of IL-1β 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Airway microbiota similar to asthmatic patients. No differences in airway diversity between asthmatic patients and healthy controls in the composition of microbiota (Ham et al, 2021).…”
Section: Inferior Airwaymentioning
confidence: 93%